Burkina Faso : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
Burkina Faso has set up ambitious developmental goals and outlined policies and reforms to reach these goals under the Strategy for Accelerated Growth and Sustained Development (SCADD). It is recognized that poverty alleviation is a long-term challenge, and there is greater scrutiny of the implementation process to ensure effectiveness. It will be important to increase the priority given to good governance, accountability, and inclusive growth. The main objective is to achieve strong and sustained economic growth. The Executive Directors encourage the government to address the shortcomings identified.